2023
DOI: 10.3390/antiox12030696
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into the Neuroprotective and Antibacterial Effects of Phlorotannins Isolated from the Cell Walls of Brown Algae Fucus vesiculosus and Pelvetia canaliculata

Abstract: Phaeophyceae (brown algae) essentially contribute to biotopes of cold and temperate seas. Their thalli are rich in biologically active natural products, which are strongly and universally dominated with phlorotannins—polyphenols of complex and diverse structure based on multiple differently arranged phloroglucinol units and well known as strong antioxidants with a broad spectrum of biological activities. In the algal cells, phlorotannins can either accumulate in the cytoplasm or can be secreted into the cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Notably, only the intracellular fraction of phlorotannins, but not the CW-bound one, increased in the air-exposed Pelvetia cells (Figure 6). This corresponds well to the results of our previous studies, where we showed that these two subcellular pools of phlorotannins differ in their molecular composition, and that free radical scavenging activity of the CW-bound phlorotannins of P. canaliculata is substantially lower compared to that of the intracellular phlorotannins [60,61]. Generally, among studied fucoid algae, P. canaliculata is distinguished by its unusually complex phlorotannin profile, which was suggested to reflect both adaptation of this species to high intertidal conditions and interaction with the endophyte fungus [60,62].…”
Section: Discussionsupporting
confidence: 92%
“…Notably, only the intracellular fraction of phlorotannins, but not the CW-bound one, increased in the air-exposed Pelvetia cells (Figure 6). This corresponds well to the results of our previous studies, where we showed that these two subcellular pools of phlorotannins differ in their molecular composition, and that free radical scavenging activity of the CW-bound phlorotannins of P. canaliculata is substantially lower compared to that of the intracellular phlorotannins [60,61]. Generally, among studied fucoid algae, P. canaliculata is distinguished by its unusually complex phlorotannin profile, which was suggested to reflect both adaptation of this species to high intertidal conditions and interaction with the endophyte fungus [60,62].…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that they may be useful as effective antioxidants in neurodegenerative diseases like AD, where oxidative stress plays a crucial role in disease progression. Phlorotannins were recently extracted from the cell walls of Pelvetia canaliculate and Fucus vesiculosus to examine their antioxidant and neuroprotective effects on cell culture models of AD and Parkinson’s Disease (PD) [ 41 ]. These cell wall-bound phlorotannins demonstrated comparable neuroprotective effects to their intracellular fractions, with less cytotoxicity but milder antioxidant activity, indicating that they may be promising candidates for therapeutic applications in neurodegenerative diseases [ 41 ].…”
Section: Neuroprotective Effects Of Macroalgae- and Microalgae-derive...mentioning
confidence: 99%
“…Phlorotannins were recently extracted from the cell walls of Pelvetia canaliculate and Fucus vesiculosus to examine their antioxidant and neuroprotective effects on cell culture models of AD and Parkinson’s Disease (PD) [ 41 ]. These cell wall-bound phlorotannins demonstrated comparable neuroprotective effects to their intracellular fractions, with less cytotoxicity but milder antioxidant activity, indicating that they may be promising candidates for therapeutic applications in neurodegenerative diseases [ 41 ]. On the other hand, phlorotannins isolated from brown seaweed, such as eckol, dieckol, and bieckol, have been shown to have anti-inflammatory properties.…”
Section: Neuroprotective Effects Of Macroalgae- and Microalgae-derive...mentioning
confidence: 99%
“…The recent study of Meshalkina et al [ 103 ] assessed the anti-neurodegenerative activity of phlorotannin extracted from F. vesiculosus and Pelvetia canaliculata for differentiated SH-SY5Y cells. The extracts of both brown algae showed modest but significant protective effects in the paraquat cell model of PD.…”
Section: Seaweed Polyphenols As Neuroprotective Antioxidantsmentioning
confidence: 99%